Implementation of Good Governance in Improving the Quality of Public Services at the Fatuaruin Village Office, Sasitamean District, Malaka District - LINO, Maria M.; LAU, Yoanita Vianney; TODA, Hendrik (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to determine the application of good governance in improving the quality of public services at the Fatuaruin Village Office, Sasitamean District, Malaka Regency. This research uses descriptive research methods with a qualitative approach. The number of informants was seven people using purposive sampling techniques. Data collection techniques include observation, interviews and documentation. Data reduction, comparative analysis, and conclusion are the data analysis techniques used. This research indicates that implementing good governance to improve public services at the Fatuaruin village office, Sasitamean subdistrict, Malaka district can be improved from aspect (1). Several services still need to be maximized in delivering information (2). Responsiveness. The community assesses that village officials have yet to respond optimally to services. (3). Regarding fairness, the community believes that village officials must be fairer in providing services because people often receive unequal services, and illegal levies occur to get maximum service from the authorities. (4) Effectiveness and efficiency: The community believes that village officials must be more effective and efficient in providing services because the community is often slow to receive services and must comply with predetermined standards, thus making the community feel disadvantaged regarding time and costs. The obstacles faced by the Fatuaruin Village government, Sasitamean District, and Malaka Regency in implementing good governance are Limited resources, lack of awareness and understanding of village officials about good governance, lack of community involvement, Corruption and nepotism.